(untitled) (ENTHYMEMA, 2024)
This article examines the connection between early scientific ideas and It-Narratives in Britain over the long eighteenth century. A set of It-Narratives - fictional texts narrated by, or centred on, non-human entities like things or animals - will be read against the attempt to detect the voice of natural things by a number of early-modern experimental and natural philosophers. It will be argued that, although causal links are hard to prove, there is a degree of epistemic vicinity between these early scientific ideas and It-Narratives. In particular, it will be shown how in both disciplines fiction helped contemplate the possibility that non-human knowledge is more reliable than human-derived one.